PHARMACOECONOMIC ANALYSIS OF VESOMNI (SOLIFENACIN AND CONTROLLED RELEASE TAMSULOSIN) TREATMENT OF STORAGE SYMPTOMS ASSOCIATED WITH BENIGN PROSTATIC HYPERPLASIA - N. A. Avxentyev; M. Yu. Frolov (IRBIS LLC, 2016)
The aim of the current study is pharmacoeconomic evaluation of using combined drug Vesomni (controlled release tablets tamsulosin 0.4 mg + solifenacin 6 mg) for treatment of patients with storage symptoms associated with benign prostatic hyperplasia, who do not respond to first line tamsulosin therapy.Materials and methods. We consider three therapy options: 1) combined drug Vesomni; 2) combination of tamsulosin (modified release capsules 0.4 mg) and solifenacin (5 mg); 3) combination of tamsulosin (controlled release tablets 0.4 mg) and solifenacin (5 mg). These options are evaluated with cost minimization and budget impact analysis.Results. We found that approx. 250,000 patients in Russia need combined tamsulosin and solifenacin therapy, including 35,400 patients eligible for government reimbursement. Using combined drug is cost saving alternative that annually requires 22,000 rubles per patient, which is 2,000 rubles less than second best option. The overall healthcare annual expenses of using combined drug are 5,7 billion rubles (500 million rubles less than for second best option), and government reimbursement costs are 606 million rubles (74 million less than for second best option).Conclusion. Using combined drug Vesomni for treatment of patients with storage symptoms associated with benign prostatic hyperplasia is cost saving alternative compared to combination of monotheraphy regimens.